Relasi Media-Negara-Masyarakat dan Pasar dalam Era Reformasi - Wahyuniï€ª, Hermin Indah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2000)
The withdrawal of state domination does not necessarily lead to the institutionalization of market. Freedom of information also requires a new kind of societal conduct. Indonesia currcntly faces tension in settling a triangular relationship between state, market and the society